KNOWLEDGE, PRACTICE OF DENGUE PREVENTION AMONG FIRST-YEAR STUDENTS OF BACH MAI MEDICAL COLLEGE IN 2024 (Vietnam Journal of Community Medicine, 2026)
Background: Dengue fever epidemics occur very complicatedly in annual cycles, the number of cases tends to increase, improving knowledge of disease prevention practices for students is very important, especially first-year students.Objectives: 1) Describe practical knowledge of dengue prevention among first-year students at Bach Mai Medical College in 2024; 2) Identify some factors related to knowledge and practice of dengue fever prevention of the research subjects.Materials and method: Cross-sectional descriptive study, conducted on 315 first-year students using the convenience sampling method from December 2023 to July 2024 at Bach Mai Medical College.Results: Through a survey of 315 first-year students, 18.73% of students had satisfactory knowledge of dengue fever prevention and 45.08% of students had satisfactory practice in dengue fever prevention. The study found an inverse relationship between knowledge and practice and a relationship between ethnicity and knowledge (p